Effective ways of supporting patients to stop smoking. Issue 2 (February 2017) - Pang, Elizabeth; Stern, Myra
Abstract : Smoking cessation is the most cost‐effective intervention for the prevention and treatment of smoking‐related diseases. This article discusses the treatments available to support smokers to stop smoking and their efficacy.